HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG KB 3 BULAN TERHADAP KEPATUHAN JADWAL SUNTIK DI DESA SUDIREJO KECAMATAN NAMO RAMBE - Ika Wijayanti (LPPM Widyagama Husada Malang, 2024)
Family planning (KB) is one of the most basic and primary preventive health services. To optimize the health benefits of family planning, these services must be provided for women by combining and fulfilling the needs of the main reproductive health services and others. In addition, reproductive health services are also responsive to various stages of a woman's reproductive life. Improving and expanding family planning services is one of the efforts to reduce the high maternal morbidity and mortality due to pregnancy experienced by women. This type of research is an analytic study with a cross-sectional study design that is used to determine the relationship between knowledge and attitudes of mothers about 3-month injection contraception against adherence to repeat injection schedules. The research was carried out in Sudirejo Village, Namo Rambe District, Deli Serdang Regency in January-July 2022 where the number of samples was 38 people by taking total sampling.